Chemo-chromism in an orthogonal dabco-based Co(ii) network assembled by methanol-coordination and hydrogen bond formation. Issue 23 (18th May 2018) - Shiga, Misaki; Kawaguchi, Shogo; Fujibayashi, Masaru; Nishihara, Sadafumi; Inoue, Katsuya; Akutagawa, Tomoyuki; Noro, Shin-ichiro; Nakamura, Takayoshi; Tsunashima, Ryo
Abstract : A newly prepared Co-based complex showed chromism by desorption of a coordinative solvent. Structural details and desorption/adsorption processes are discussed in depth. Abstract : Newly prepared single crystals of [Co(ii )(dabco)(NCS)2 (MeOH)2 ]·dabco (1-pink ; dabco: 1, 4-diazabicyclo[2.2.2]octane) showed chromotropic behaviour in the solid state, changing from pink to blue upon heating or grinding. The complex1-pink exhibited a two-dimensional orthogonal network structure with the coordination chain of –dabco–Co– bridged by hydrogen bonds between coordinative methanol and a second dabco molecule, where the methanol molecule was trapped by coordinative and hydrogen bonds. Chromism was demonstrated to stem from the quantitative desorption of methanol from1-pink to produce [Co(ii )(dabco)(NCS)2 ]·dabco (1-blue(c) ) by thermogravimetric (TG) and temperature controlled gas chromatography-mass spectrometry (GC-MS) analyses, and powder X-ray diffraction (XRD) analysis suggests that the transformation between the crystalline phases of1-pink and1-blue(c) occurred with similar lattice parameters. Furthermore, the desolvated species showed chemo-chromic behaviour due to the selective size- and polarity-dependent adsorption of solvent molecules.